Dialoguing the Qur'an's Pronoun (Damir) and Gender Equality - Akhmad Luthfi Mubarok (Journal Of Social Science (JoSS), 2025)
This study examines the emergence of damir and analyzes its distribution across 114 surahs of the Qur'an to address key questions regarding the relationship between the use of damir, the adaptation of damir to the phenomenon of taghlib, and the discourse on gender equality. It employs a mixed-methods approach based on full corpus analysis, combined with the spirit of maqasid al-shari'ah, and engages perspectives from both classical and contemporary Islamic thinkers, as well as hermeneutics scholars concerned with this issue. The findings show that the form and occurrence of damir do not indicate the superiority of any gender; rather, they must be understood according to the linguistic rule of taghlib. The study concludes that the distribution of damir in the Qur'an represents a divine communication strategy that avoids gender bias in Qur'anic language, a conclusion that can be demonstrated through scientific analysis.